THE EXISTENCE OF ISLAMIC SCHOOL EDUCATION IN PREVENTING TERRORISM IN ISLAMIC BOARDING SCHOOL OF AL-MUKMIN NGRUKI SOLO - Al Qifari, Abudzar; Arsyad, Azhar; Damopolii, Muljono; Salenda, Kasjim (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
This research aims at revealing the existence of Islamic school education in preventing terrorism in Islamic boarding school of Al-Mukmin Ngruki Solo. This qualitative research involved the Director of PPIM, Head of PPIM, Educators, Education Personnel, Head of Dormitory, Santri (students), and Santri’s Parents. The data collection method in this study were observation, interview, and documentation. The research instruments were the researchers themselves. The results revealed that the curriculum used was KTSP 2013 and the system was a modern Islamic boarding school, but the reason why the Islamic boarding school was labeled as the place of terrorism cadres due to the alumni who became suspects in the Bali bombings and its founder became a suspect as well. The supporting factor is from the alumni association that is needed by the community and the inhibiting factor did not exist at all. Abstrak: Penelitian ini bertujuan untuk mengungkap keberadaan pendidikan pesantren dalam pencegahan terorisme di Pondok Pesantren Al-Mukmin Ngruki Solo. Penelitian kualitatif ini melibatkan Direktur PPIM, Kepala PPIM, Pendidik, Tenaga Kependidikan, Kepala Asrama, Santri, dan Orang Tua Santri. Metode pengumpulan data dalam penelitian ini adalah observasi, wawancara, dan dokumentasi. Instrumen penelitian adalah peneliti itu sendiri. Hasil penelitian menunjukkan bahwa kurikulum yang digunakan adalah KTSP 2013 dan sistemnya adalah pesantren modern, namun alasan pesantren dicap sebagai tempat kader terorisme karena alumni yang menjadi tersangka bom Bali dan pendirinya. juga menjadi tersangka. Faktor pendukungnya adalah dari ikatan alumni yang dibutuhkan masyarakat dan faktor penghambatnya tidak ada sama sekali.